2006
DOI: 10.1111/j.1528-1167.2006.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypermotor Seizures, Suggesting Frontal Lobe Epilepsy, Can Originate in the Insula

Abstract: Summary: Purpose:To report three patients with drugresistant nocturnal hypermotor seizures (NHSs), no detectable brain lesion, and clinically defined nocturnal frontal lobe epilepsy (NFLE) or autosomal dominant NLFE (ADNFLE), whose intracerebral EEG ictal onset primarily involved the insula, rather than the mesial or orbital frontal cortex.Methods: Fourteen to 15 intracerebral electrodes were implanted in each patient, primarily sampling the frontal lobes with 80 to 91 recording leads covering the most likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(187 citation statements)
references
References 41 publications
8
175
0
4
Order By: Relevance
“…It may be that upstates that originate in these areas are better able to propagate to other cortical areas and manifest on the scalp. This agrees with the observation that the area around the lateral sulcus is important for the initiation and propagation of seizures in many cases of temporal lobe epilepsy (42,43). Intriguingly, patients with insular strokes report significantly more tiredness than patients with similar strokes that do not involve the insula (44).…”
Section: Origins Propagation and Involvement Each Reveal Novel Infosupporting
confidence: 79%
“…It may be that upstates that originate in these areas are better able to propagate to other cortical areas and manifest on the scalp. This agrees with the observation that the area around the lateral sulcus is important for the initiation and propagation of seizures in many cases of temporal lobe epilepsy (42,43). Intriguingly, patients with insular strokes report significantly more tiredness than patients with similar strokes that do not involve the insula (44).…”
Section: Origins Propagation and Involvement Each Reveal Novel Infosupporting
confidence: 79%
“…21 Desde este relato, vários tipos de epilepsias têm sido descritos com origem cortical e etiologias variáveis, as quais se apresentam com crises, exclusiva ou predominantemente, durante o sono. 22,23 Uma série de publicações voltou-se para este ponto sugerindo que alguns tipos de malformações do desenvolvimento cortical, mais especificamente displasia cortical focal tipo II, conforme classificação de Palmini e colaboradores, 12 estão mais associadas a anormalidades epilépticas relacionadas ao sono, não somente em função da refratariedade das crises, como também pela presença dos surtos curtos recorrentes pseudoperiodicamente organizados ocorrendo durante o sono de ondas lentas. 24,25 Esta é uma área ainda incipiente e grupos diferentes relataram resultados diferentes, em consequência à inclusão de casos não homogêneos e provavelmente a questões metodológicas envolvidas.…”
Section: Fisiopatologia E Definições: Sono E Epilepsiaunclassified
“…47,48 EPILEPSIA DESENvOLvIMENTAL E SONO O interesse pelas lesões do desenvolvimento, especialmente as malformações corticais, aumentou nas últimas décadas incentivado pelos avanços em neuroimagem e em biologia molecular, tornando o eixo etiológico mais evidente e sugerindo que ao invés da (ou em adição a) topografia, a etiologia pode estar relacionada à probabilidade de ocorrência de epilepsia relacionada ao sono. 23,24,49 Muitas anormalidades estruturais foram reconhecidas e classificadas e as malformações do desenvolvimento cortical são as que mais se relacionam a crises epilépticas. Elas diferem de outras anormalidades estruturais por possuirem diferentes graus de excitabilidade cortical e potencial para gerar crises clínicas associadas à disfunção motora e cognitiva.…”
Section: Microestrutura Do Sono E Epilepsiasunclassified
“…Paroxysmal arousals, dystonia-like attacks, and epileptic nocturnal wanderings are also part of the phenotype [120]. Ictal video-EEG studies have revealed partial seizures originating from the frontal lobe, but also from parts of the insula and temporal lobe, suggesting a defect of a broader network [121,122]. A mutation in the gene CHRNA4, encoding the α4-subunit of a neuronal nicotinic acetylcholine receptor (nAchR), was the first ion channel mutation found in an DS Dravet syndrome; ID intellectual disability; IS infantile spasms;…”
Section: Autosomal Dominant Nocturnal Frontal Lobe Epilepsymentioning
confidence: 99%